Lyapunov instability of stationary flows of a polymeric fluid in a channel with perforated walls. (1st March 2022) - Blokhin, A. M.; Tkachev, D. L.
Abstract: The rheological Pokrovskii-Vinogradov model for flows of solutions or melts of an incompressible viscoelastic polymeric medium is studied in the case of flows in an infinite planar channel with perforated walls. The linear Lyapunov instability is proved for the base solution with constant flow rate in the class of perturbations periodic in the variable varying along the channel wall. Bibliography: 14 titles.